Gestão ambiental participativa : contribuições de comunidades de bairros em áreas urbanas de riscos à saúde - Moitinho, Ana Caroline Figueiredo (2017)
This study addresses the importance of neighborhood residents’ participation in environmental management of health units in urban areas facing environmental risks. Public environmental management of basic health systems is discussed, furthermore an epidemiological field study and its relationships with participatory environmental management are presented. The empirical field of this study was the Rosa Elze neighborhood, in São Cristóvão, Sergipe. Forty individuals aged 20 through 75 years participated in this study, being 26 women and 14 men. The research is classified as descriptive and exploratory, and the main data collection instruments were: systematic observation, semi-structured interviews, service satisfaction scale, and photographic analysis. According to the results, neighborhood residents can collaborate to greater efficiency, effectiveness, and directivity regarding environmental problem control in urban risk areas, especially about prevention and direct intervention of epidemiological cases. Additionally, it is pertinent to highlight the need for technical and scientific studies, in the environmental management field, towards the development of participative environmental management instruments to diagnosis, intervention, and prognosis that favor participation, interaction, and collaboration between health basic units and neighborhood residents in urban areas.